Dukungan Keluarga Berhubungan dengan Tingkat Kecemasan pada Pasien Pre Operasi Orif Fraktur Ekstremitas Bawah di RS Ortopedi Prof. Dr. R. Soeharso Surakarta - Siti Nurul Kholifa; Agung Widiastuti; Insanul Firdaus (Fakultas Ilmu Kesehatan, 2026)
Lower limb fractures often require surgical intervention, which can cause significant pre-operative anxiety due to uncertainty, pain and the recovery process. Family support is believed to be critical in helping patients manage this anxiety. This study aims to determine whether there is a relationship between family support and anxiety levels in pre-operative ORIF (Open Reduction Internal Fixation) patients with lower extremity fractures. This research is a correlative analytic study with a cross-sectional design. The sample was selected using purposive sampling technique, with a total sample size of 35 respondents. Data collection was carried out using a validated questionnaire, namely the family support questionnaire and the Hamilton Anxiety Rating Scale (HARS) to measure anxiety levels that have gone through validity and reliability tests. Data were analyzed using the Spearman Rank test. The majority of respondents (94.3%) received high family support, while 5.7% received moderate family support. A total of 45.7% of patients did not experience anxiety, 45.7% experienced mild anxiety, and 8.6% experienced severe anxiety. The results of the analysis using the Spearman Rank test showed a significant relationship between family support and anxiety levels in ORIF pre-operative patients. The results showed a significant relationship between family support and the anxiety levels of patients undergoing preoperative ORIF procedures, with a correlation coefficient of -0.434 and a significance value of 0.009 (P < 0.05).